Magnetic carbon fiber material as well as preparation method and application thereof

By synthesizing the magnetic carbon fiber material Fe3O4@MWCNTs@poly(GMA-co-TRIM) with core-shell structure, the problems of low efficiency and high cost of the existing magnetic solid-phase extraction materials in the enrichment of cannabinoid drugs in wastewater are solved, and efficient, fast and economical detection results are achieved.

CN119897067APending Publication Date: 2025-04-29CHINA PHARM UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411935936.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing magnetic solid phase extraction materials have problems of long time, low efficiency and high cost in enriching cannabinoid drugs, which are difficult to meet the needs of sewage detection.

Method used

A magnetic carbon fiber material Fe3O4@MWCNTs@poly(GMA-co-TRIM) with a core-shell structure was designed and synthesized. Through ultrasonic dispersion and magnetic field separation technology, efficient adsorption and enrichment of trace synthetic cannabinoid drugs in wastewater can be achieved.

Benefits of technology

This material significantly improves the detection sensitivity of synthetic cannabinoid drugs in sewage, simplifies pretreatment steps, realizes high-throughput automated detection, and is low in cost and shorter enrichment time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211511690000071
    Figure BDA0005211511690000071
  • Figure BDA0005211511690000072
    Figure BDA0005211511690000072
  • Figure BDA0005211511690000081
    Figure BDA0005211511690000081
Patent Text Reader

Abstract

The invention discloses a magnetic carbon fiber material as well as a preparation method and application thereof. The magnetic carbon fiber material is Fe3O4 (at) MWCNTs (at) poly (GMA-co-TRIM) with a core-shell structure, wherein the Fe3O4 is located at the core, the outer layer of the Fe3O4 is wrapped with a core-shell layer MWCNTs formed by carboxylated multi-walled carbon nanotubes, and the outer part of the core-shell layer of the MWCNTs is wrapped with a load layer of polyglycidyl methacrylate crosslinked trimethylolpropane trimethacrylate (GMA-co-TRIM). The magnetic carbon fiber material Fe3O4 (at) MWCNTs (at) poly (GMA-TRIM) has the advantages of being easy and convenient to operate, environmentally friendly and capable of being combined with on-site rapid detection or large instrument detection and analysis, and high-flux automatic detection of synthetic cannabinoid in sewage can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a magnetic carbon fiber material and a preparation method and application thereof, and in particular to a magnetic carbon fiber material for detecting synthetic cannabinoid drugs in sewage and a preparation method and application thereof, belonging to the technical field of chemical detection. Background Art

[0002] Synthetic drugs are increasingly dominating the illegal drug use market due to their low production costs, the use of various precursors rather than fixed crops in the planting area, and the rapid replacement of seized drugs. Synthetic cannabinoids (SCs) are mainly inhaled by burning synthetic cannabinoids sprayed on plant-based materials. This ingestion method does not go through the first-pass effect of the liver, and can quickly make the blood drug concentration in the user reach a peak, but it is metabolized quickly in the human body. For example, the blood drug concentration of JWH-018 and JWH-073 will reach a peak within 5 minutes after inhalation, and then drop to less than one-tenth of the maximum concentration within 3 hours. It exists in urine at a concentration of pg / mL and is discharged into domestic sewage. Therefore, it is of great significance to detect synthetic cannabinoids in sewage.

[0003] Sewage epidemiology refers to analyzing the concentration of chemical substances in the influent of sewage treatment plants, estimating the pattern of consumption of certain chemical substances by the population in the area based on the human metabolic mechanism, influent flow rate and the number of people served, investigating the public information such as diseases, consumption and health related to the substances, so as to prevent and control related diseases. At present, sewage epidemiology has been widely used in the investigation of illegal addictive substance abuse, including the investigation of the abuse of illegal drugs such as synthetic cannabinoids, amphetamines, cocaine, heroin, etc., and is one of the commonly used methods of drug abuse monitoring.

[0004] Since the sewage collected through the sewage treatment plant inlet has complex components and low concentration of target substances, it must be pre-treated. At present, the detection of ultra-trace drugs and new psychoactive substances in sewage includes HPLC-MS / MS method, GC-MS method, etc. In order to improve the sensitivity of detection and reduce the matrix effect, these methods usually need to be combined with sample pretreatment methods to enrich the target detection objects, such as liquid-liquid extraction (LLE), solid phase extraction (SPE), solid phase microextraction (SPME), magnetic solid phase extraction (MSPE), liquid-liquid microextraction (LPME), etc. Among them, solid phase extraction is the most widely used pretreatment method, which has the characteristics of high degree of commercialization, high efficiency, reliability, and less use of liquid reagents. However, solid phase extraction columns are expensive, with many types of fillers, poor specificity and complicated operation steps; solid phase microextraction does not require solvents to directly extract volatile and semi-volatile compounds in aqueous solutions and solid matrices, but the surface of quartz fibers is The thickness of the solid-liquid film has an impact on the solid-phase adsorption amount and equilibrium time of the analyte, which can easily cause inaccurate experimental results; liquid-liquid extraction does not require special equipment, is simple and fast to operate, and can be used for solid samples. It is mostly used in the fields of petroleum, metallurgy, food, medicine and environmental protection, but the liquid-liquid extraction method requires a large amount of organic reagents, which is not environmentally friendly. When there are highly water-soluble components in water, it is difficult to extract and emulsification is prone to occur; compared with liquid-liquid extraction, liquid-liquid microextraction uses less organic solvents and is more environmentally friendly, but the enrichment effect of the target in a complex matrix is ​​worse than that of the target in a single matrix; magnetic solid-phase extraction has the characteristics of easy operation, small volume of organic solvent used, close contact with the target analyte, and significantly improved extraction efficiency. It has been successfully used in the analysis of environmental, biological and food matrices. However, the existing magnetic solid-phase extraction materials have long enrichment time, low enrichment efficiency and high cost, so it is necessary to develop new magnetic solid-phase extraction materials with shorter enrichment time, higher enrichment efficiency and lower cost. Summary of the invention

[0005] Purpose of the invention: The first purpose of the present invention is to provide a magnetic carbon fiber material. The second purpose of the present invention is to provide a method for preparing the magnetic carbon fiber material. The third purpose of the present invention is to provide an application of the magnetic carbon fiber material in detecting synthetic cannabinoid drugs in sewage.

[0006] Technical solution: The present invention discloses a magnetic carbon fiber material, which is a core-shell structured Fe3O4@MWCNTs@poly (GMA-co-TRIM); wherein Fe3O4 is located in the core, and the outer layer of Fe3O4 is wrapped with a core-shell MWCNTs formed by carboxylated multi-walled carbon nanotubes, and the outside of the MWCNTs core-shell layer is wrapped with a load layer of poly(glycidyl methacrylate) cross-linked trimethylolpropane trimethacrylate (GMA-co-TRIM).

[0007] The method for preparing the magnetic carbon fiber material of the present invention comprises the following steps:

[0008] (A1) dissolving carboxylated multi-walled carbon nanotubes in deionized water and dispersing the carbon nanotubes by ultrasonication to obtain a carboxylated multi-walled carbon nanotube suspension;

[0009] (A2) dissolving ferric chloride hexahydrate and sodium dodecyl sulfate in deionized water, dissolving by ultrasonication, adding ferrous chloride tetrahydrate and carboxylated multi-walled carbon nanotube suspension, stirring to dissolve, adjusting the pH, stirring to react under nitrogen protection, separating and collecting under the action of an external magnetic field, washing with deionized water and anhydrous ethanol for multiple times, and vacuum drying to obtain Fe3O4@MWCNTs;

[0010] (A3) Fe3O4@MWCNTs were dissolved in acetonitrile, ultrasonically dispersed, glycidyl methacrylate (GMA) and trimethylolpropane trimethacrylate (TRIM) were added, the mixture was stirred and heated, 2,2-azobisisobutyronitrile (AIBN) was added, the mixture was heated and stirred for reaction, and the mixture was washed with acetonitrile and deionized water for multiple times and vacuum dried to obtain

[0011] Fe3O4@MWCNTs@poly(GMA-co-TRIM).

[0012] Furthermore, in step (A1), the concentration of the carboxylated multi-walled carbon nanotube suspension is 0.08 g / mL.

[0013] Furthermore, in step (A2), the mass ratio of ferric chloride hexahydrate, sodium dodecyl sulfate, ferrous chloride tetrahydrate and carboxylated multi-walled carbon nanotubes is (3-5):0.1:(1-3):(1-2), preferably 4.7:0.1:1.72:2.

[0014] Furthermore, in step (A2), the pH is adjusted to 11±0.5.

[0015] Furthermore, in step (A2), the stirring reaction time under nitrogen protection is more than 60 minutes.

[0016] Furthermore, in step (A2), the substrate is washed with deionized water and anhydrous ethanol for more than three times.

[0017] Furthermore, in step (A2), the vacuum drying temperature is 60-70° C., and the vacuum drying time is 8-16 hours.

[0018] Furthermore, in step (A3), the mass ratio of Fe3O4@MWCNTs, glycidyl methacrylate, trimethylolpropane trimethacrylate and 2,2-azobisisobutyronitrile is 200:(70-280):(140-560):(6-24).

[0019] Furthermore, in step (A3), the temperature is raised to 70±5° C. with stirring.

[0020] Furthermore, in step (A3), the temperature of the heating and stirring reaction is 70±5° C., and the time of the heating and stirring reaction is 4 to 24 hours.

[0021] Furthermore, in step (A3), washing is performed with acetonitrile and deionized water for more than three times.

[0022] Furthermore, in step (A3), the vacuum drying temperature is 60 to 70° C., and the vacuum drying time is 8 to 16 hours.

[0023] The magnetic carbon fiber material of the present invention is used in detecting synthetic cannabinoid drugs in sewage.

[0024] Further, the synthetic cannabinoid drugs are 1(-4-cyanobutyl)-N-(1-methyl-1-phenylethyl)-1H-indazole-3-carboxamide (4CN-CUMYL-BUTINACA), N-[[4-fluorobutyl)-1H-indazole-3-yl]carbonyl]-3-methyl-L-valine methyl ester (4F-MDMB-BUTINACA), (2S)-2-[[1-(5-fluoropentyl)indole-3-carbonyl]amino]-3,3-dimethylbutanoic acid methyl ester (5F-MDMB-PICA), 2-[[1-[5-fluoropentyl]indole-3-carbonyl]amino]-3-phenylpropionic acid methyl ester (5F-MPP-PICA), (1(-pent-4-en-1-yl)-1H-indole-3-carbonyl)-L-valine methyl ester (AMB-4en-PICA), N-[1-(cyclohexyl)- methyl)-1H-indole-3-carbonyl] valine methyl ester (AMB-CHMICA), (2S)-2-[[1-[(4-fluorophenyl)methyl]indole-3-carbonyl]amino]-3-methylbutanoic acid methyl ester (AMB-FUBICA), (1(-4-fluorobenzyl)-1H-indol-3-yl)(2,2,3,3-tetramethylcyclopropyl)methanone (FUB-144), N,-(1- (2S)-2-[[1-[(4-fluorophenyl)methyl]indole-3-carbonyl]amino]-3,3-dimethylbutyric acid methyl ester (MDMB-FUBICA).

[0025] The present invention also includes a method for detecting synthetic cannabinoid drugs in sewage, comprising the following steps:

[0026] (B1) adding the magnetic carbon fiber material according to claim 1 to the wastewater with adjusted pH, extracting by uniform shaking, separating by adding a magnet, and eluting by adding an eluent to obtain an eluent;

[0027] (B2) Ultrapure water was added to the eluent and used for UHPLC-MS / MS injection detection.

[0028] Furthermore, in step (B1), the volume mass ratio of sewage to the liquid magnetic carbon fiber material of the present invention is 100: (5-40) mL / mg.

[0029] Furthermore, in step (B1), the pH of the sewage is adjusted to 2-4.

[0030] Furthermore, in step (B1), the eluent is acetonitrile, methanol, a mixture of aqueous ammonia and methanol, a mixture of aqueous ammonia and acetonitrile, acetic acid methanol, and a mixture of acetic acid and acetonitrile, preferably acetonitrile.

[0031] Furthermore, in step (B1), the time of uniform shaking extraction is more than 20 minutes.

[0032] Furthermore, in step (B1), the volume ratio of sewage to eluent is 100:(100-1000) mL / μL.

[0033] Furthermore, in step (B1), the elution time is 1 to 4 minutes.

[0034] Further, in step (B2), during UHPLC-MS / MS detection, the liquid chromatography conditions are: the chromatographic column is Thermo BDSHYPERSIL C18; 0.1% formic acid aqueous solution is used as mobile phase A, and acetonitrile is used as mobile phase B; gradient elution: 0-4 min, 15→30% A, 4-5 min, 30% A, 5-7 min, 30→15% A, and the column temperature is 40°C; the flow rate is 0.3 mL / min; the injection volume is 10 μL; the mass spectrometry conditions are: the ion source is an ESI electrospray ion source; the spray voltage is 3500 V; the sheath gas flow rate is 30 Arb; the auxiliary gas flow rate is 10 Arb; the ion transfer tube temperature is 325°C; the nebulization temperature is 150°C; and the scanning mode is MRM.

[0035] The present invention designs and synthesizes a core-shell magnetic particle Fe3O4@MWCNTs@poly(GMA-co-TRIM) double-modified with carboxylated multi-walled carbon nanotubes and poly(GMA-co-TRIM). The material combines the excellent high surface area of ​​carboxylated multi-walled carbon nanotubes (MWCNTs) and the functional characteristics of poly(GMA-co-TRIM), and achieves efficient and specific adsorption of synthetic cannabinoid drugs. The preparation method is simple and easy to operate, and can be used in the detection process of synthetic cannabinoid drugs distributed in sewage by adsorbing trace amounts of synthetic cannabinoid drugs.

[0036] The magnetic carbon fiber material synthesized by the present invention adopts a core-shell structure, that is, Fe3O4@MWCNTs is used as the central core, and a poly(glycidyl methacrylate) cross-linked trimethylolpropane trimethacrylate layer is wrapped in the outer layer to enhance its adsorption capacity and adsorption stability. The magnetic carbon fiber material can be evenly dispersed in water with the assistance of ultrasound, which increases the contact between the magnetic carbon fiber material and the target analyte in sewage. The poly(GMA-co-TRIM) layer adsorbs the target through hydrophobic, hydrogen bonding and electrostatic adsorption. The magnetic carbon fiber material can adsorb synthetic cannabinoid drugs in sewage samples, proving that this material has a good adsorption and separation effect on synthetic cannabinoid drugs, and can be used to detect the content of synthetic cannabinoid drugs in sewage.

[0037] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0038] The Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in the present invention has a relatively simple process for treating trace amounts of synthetic cannabinoid drugs in complex matrix samples, can greatly improve the sensitivity of instruments in detecting synthetic cannabinoid drugs, can be used in conjunction with on-site rapid detection instruments or large-scale laboratory analysis instruments, reduces pre-treatment steps, avoids the shortcomings of complex steps and low repeatability in the past, and realizes high-throughput automated detection of trace drugs in sewage. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Transmission electron micrographs of Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber materials prepared in Example 1;

[0040] Figure 2 FT-IR images of Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber materials prepared in Example 1;

[0041] Figure 3This is the room temperature hysteresis loop diagram of the Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in Example 1;

[0042] Figure 4 The XPS full spectrum of Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in Example 1 and the characterization diagrams of C, O and Fe;

[0043] Figure 5 This is a graph showing the MSPE-LC-MS / MS test results of 11 synthetic cannabinoid drugs in Example 2;

[0044] Figure 6 This is a graph showing the effect of different Fe3O4@MWCNTs and GMA dosage ratios on the magnetic solid phase extraction adsorption of the target in Example 3;

[0045] Figure 7 This is a graph showing the effect of different Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesis times on the magnetic solid phase extraction adsorption of the target in Example 4;

[0046] Figure 8 This is a result diagram showing the effect of pH value of sample wastewater on magnetic solid phase extraction adsorption in Example 5;

[0047] Fig. 9 This is a result diagram showing the effect of the amount of magnetic carbon fiber material used in the magnetic solid phase extraction elution step on the magnetic solid phase extraction adsorption in Example 6;

[0048] Fig.10 This is a result diagram showing the effect of adsorption time on magnetic solid phase extraction adsorption in the magnetic solid phase extraction elution step in Example 6;

[0049] Fig.11 This is a graph showing the effect of different elution solvents on magnetic solid phase extraction adsorption in the magnetic solid phase extraction elution step in Example 7;

[0050] Fig.12 This is a result diagram showing the effect of the volume of the elution solution on the magnetic solid phase extraction adsorption in the magnetic solid phase extraction elution step in Example 7;

[0051] Fig.13 This is a result diagram showing the effect of elution time on magnetic solid phase extraction adsorption in the magnetic solid phase extraction elution step in Example 7;

[0052] Fig.14 This is a graph showing the effect of the inorganic ion concentration of the sample solution on magnetic solid phase extraction in Example 8;

[0053] Fig.15 This is a graph showing the effect of organic solvent concentration in the sewage solution on magnetic solid phase extraction in Example 9. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0055] Example 1 Preparation of Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material

[0056] (1) Weigh 2.00 g of carboxylated multi-walled carbon nanotubes into 25 mL of deionized water and disperse them evenly by ultrasonication to obtain a carboxylated multi-walled carbon nanotube suspension;

[0057] (2) 4.70 g of ferric chloride hexahydrate and 0.1 g of sodium dodecyl sulfate were dissolved in 50 mL of deionized water, and ultrasonically dissolved. 1.72 g of ferrous chloride tetrahydrate and carboxylated multi-walled carbon nanotube suspension were added, and the mixture was stirred and dissolved. The pH value was adjusted to 11 with ammonia water to make the reaction solution black. The reaction solution was mechanically stirred for 60 min under nitrogen protection. The obtained reaction solution was placed on a magnetic rack, and the liquid was discarded after separation. The solid product was then washed three times with deionized water and anhydrous ethanol in turn to remove the unreacted ferric chloride and carboxylated multi-walled carbon nanotubes and other substances. Finally, the obtained product was placed in a vacuum drying oven and dried at 60° C. to obtain Fe3O4@MWCNTs particles.

[0058] (3) Weigh 200 mg of the synthesized Fe3O4@MWCNTs particles and ultrasonically disperse them in 20 mL of acetonitrile. Add 70 mg of GMA and 140 mg of TRIM in sequence, stir and heat to 70°C, add 6 mg of AIBN, and mechanically stir at 70°C for 16 h. After the reaction is completed, place the resulting reaction solution on a magnetic rack, separate and discard the liquid to obtain a magnetic solid product, ultrasonically clean the magnetic solid product with acetonitrile and deionized water for 3 times, respectively, and vacuum dry at 60°C to obtain the final product, Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material.

[0059] The Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber materials prepared in this example were analyzed by transmission electron microscopy. Figure 1 shown. Figure 1 The transmission electron micrographs of Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber materials prepared in Example 1, wherein A is Fe3O4@MWCNTs and B is Fe3O4@MWCNTs@poly(GMA-co-TRIM). Figure 1It can be seen that the carboxylated multi-walled carbon nanotubes MWCNTs are hollow cylinders, and spherical Fe3O4 is attached to the surface of MWCNTs, with a particle size between 22.37-55.26nm; F after wrapping with GMA and TRIM e3 The particle size of O4@MWCNTs@poly(GMA-co-TRIM) is between 114.68nm and 157.39nm, and the increase in the particle size of the material proves that the material encapsulation is successful.

[0060] The Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber materials prepared in this example were subjected to FT-IR analysis, and the results are shown in Figure 2. According to the FT-IR comparison chart of Fe3O4@MWCNTs and Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic materials, Fe3O4@MWCNTs@poly(GMA-co-TRIM) was successfully synthesized. Figure 2 Visible, 1402cm -1 The peak at 1592 cm is the bending vibration of the OH bond. -1 The peak at 3340 cm is the stretching vibration of C=C. -1 The broad peaks on the left and right are the stretching vibrations of the OH bonds, 575 cm -1 The peak at 575cm is the stretching vibration of Fe-O, indicating that Fe3O4@MWCNTs were successfully synthesized. -1 The Fe-O stretching vibration peak at 2896 and 1450 cm-1 disappeared, indicating that Fe3O4 was covered; -1 The vibration peaks at 1702 cm indicate the CH stretching and CH bending of the polymer chain. The C=O stretching vibration of the ester group of MWCNT-g-GMA is present at 1702 cm -1 There is no C=C stretching vibration in the spectrum of MWCNT-g-GMA, which indicates that the C=C of GMA monomer is opened during the polymerization process. -1 The peak at 868 cm-1 shows the stretching of C=OO of the GMA side chain. AIBN not only acts on GMA to break its double bonds to form free radicals, but also activates multi-walled carbon nanotubes by opening π bonds, resulting in the appearance of 868 cm-1 in MWCNT-g-GMA. -1 and 790cm -1 These observations indicate that GMA is indeed grafted onto MWCNTs via free radical polymerization.

[0061] The magnetic response of the Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in this example was investigated. Figure 3 shown. Figure 3 This is the room temperature hysteresis loop of the Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in Example 1. The S-shaped hysteresis loop confirms the superparamagnetism of the synthetic material. The chemical composition and element chemical valence state of the surface of the Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in this example were analyzed by XPS, and then C1s, O1s, and Fe2p were analyzed separately. The results are as follows: Figure 4 shown. Figure 4 The XPS full spectrum of Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in Example 1 and the characterization diagrams of C, O, and Fe, where (A) is the characterization diagram of C, (B) is the characterization diagram of O, (C) is the characterization diagram of Fe, and (D) is the XPS full spectrum diagram. Figure 4 It can be seen that the strong O1s peak and C1s in the whole spectrum prove that it contains rich carbon and oxygen functional groups. The C1S spectrum shows the existence of three types of carbon bonds: CC (284.73eV), CO (286.04eV) and C=O (288.90eV). The strong O1s peak contains a large amount of CO (533.32eV) and C=O (531.78eV), as well as a part of Fe-O (529.79eV). In the high-resolution Fe2p scan, the binding energy peaks are located at 710.59eV and 724.28eV, corresponding to Fe2p3 / 2 and Fe2p1 / 2, respectively. Based on the above results, Fe3O4@MWCNTs@poly(GMA-co-TRIM) was successfully synthesized.

[0062] Example 2

[0063] The Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material prepared in Example 1 was used to detect drugs in sewage. The specific steps are as follows:

[0064] (1) Solution preparation

[0065] Preparation of reference solution of the test substance: Take 100 μL of 100 μg / mL 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA, and MDMB-FUBICA reference stock solution in a 10 mL volumetric flask, dilute to the scale with acetonitrile, and prepare 1 μg / mL reference solution respectively.

[0066] Preparation of mixed internal standard solution:

[0067] Primary stock solution: Take 100 μL of 200 μg / mL 4F-MDMB-BUTINACA-d3 solution in a 10 mL volumetric flask and dilute to the mark with methanol to prepare a 2 μg / mL primary stock solution.

[0068] Working internal standard solution: Take 500 μL of the primary stock solution, place it in a 10 mL volumetric flask, and dilute it to the mark with acetonitrile to obtain a 100 ng / mL working internal standard solution.

[0069] (2) Collection and pre-treatment of domestic sewage

[0070] 24-hour mixed sewage from the water inlets of sewage treatment plants in various places was collected by automatic water sampler, and the collected mixed sewage was placed in a 500 mL polyethylene terephthalate (PET) bottle and frozen at -20 ° C. The collected sewage has been verified as blank sewage. After thawing, an appropriate amount of the reference solution of the test object was added to obtain sewage containing different concentrations of the test object, in which the concentration of each test object was the same.

[0071] Pretreatment: Use glass fiber filter membrane to filter solid impurities in sewage, adjust the pH value of the sample solution to 2 with dilute hydrochloric acid or sodium hydroxide, measure 100 mL of sewage and place it in a PET bottle, add 100 μL of working internal standard solution and then add 20 mg of Fe3O4@MWCNTs@poly(GMA-co-TRIM), shake at a constant speed for 20 min, place on a magnet, discard the supernatant after separation, add 300 μL of acetonitrile and vortex at 1500 rpm / min for 2 min for elution, separate with a magnet, take the eluent acetonitrile and centrifuge it at a speed of 10000 rpm / min, take the supernatant after centrifugation and mix it with an equal volume of deionized water and inject it.

[0072] (3) Analysis of sample solution after pretreatment

[0073] The injected solution was analyzed by UHPLC-MS / MS (Agilent G6470A), where:

[0074] Liquid chromatography conditions: The chromatographic column was Thermo BDS HYPERSIL C18 (4.6x100 mm, 3 μm); mobile phase A was 0.1% formic acid aqueous solution, and mobile phase B was acetonitrile; column temperature was 40°C; flow rate was 0.3 mL / min; injection volume was 10 μL; gradient elution program is shown in Table 1.

[0075] Table 1 Gradient elution program

[0076]

[0077] Mass spectrometry conditions: the ion source is ESI electrospray ion source; the spray voltage is 3500 V; the sheath gas flow rate is 30 Arb; the auxiliary gas flow rate is 10 Arb; the ion transfer tube temperature is 325 ° C; the nebulization temperature is 150 ° C; the scanning mode is MRM; the MRM monitoring channel of each analyte is determined according to the mass spectrometry scanning results, see Table 2 for details.

[0078] Table 2 MRM monitoring channels for each analyte

[0079]

[0080]

[0081] The chromatograms of 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA-d3, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA, and MDMB-FUBICA are as follows Figure 5 See Figure 5 From the chromatogram, it can be seen that this method can be used to detect 11 target substances in sewage (including 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB-FUBICA).

[0082] (3) Methodological validation

[0083] The content of method validation mainly consists of linearity, accuracy, precision, recovery and matrix effect.

[0084] 1. Linear

[0085] Take an appropriate amount of the reference solution of each analyte and 100 μL of the working internal standard solution, add them to 100 mL of pure water, and prepare a solution containing 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB -FUBICA mixed simulated samples with concentrations of 5 ng / L, 10 ng / L, 25 ng / L, 50 ng / L, 100 ng / L, 250 ng / L, and 500 ng / L were processed according to the pretreatment method of step (2). Double sample analysis was performed for each concentration. 10 μL of sample was injected and the chromatogram was recorded. The ratio of the concentration of the analyte to the concentration of the internal standard was used as the horizontal axis (X), and the ratio of the peak area of ​​the analyte to the peak area of ​​the internal standard was used as the vertical axis (Y). The weighted least square method (weight coefficient: 1 / X 2 ) was used for linear regression calculation, and the linear regression equation obtained was the standard curve equation, and the correlation coefficient (r) was calculated. The results are shown in Table 3.

[0086] Table 3 Standard curves for determination of various targets in water samples by MSPE-UHPLC-MS / MS

[0087]

[0088]

[0089] The results in Table 3 show that 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB-FUBICA had a good linear relationship in the range of 5.0-500 ng / L.

[0090] 2. Accuracy and precision

[0091] The pretreatment operation in step (2) was carried out on wastewater containing 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB-FUBICA at 2.5 ng / L (lower limit of quantification), 15 ng / L, 25 ng / L and 400 ng / L, and the accuracy and precision (n=6) were investigated. The accuracy was expressed as error, and the measured concentration was calculated by linearity, and the percentage of the measured concentration and the added concentration was compared. The precision investigated the change after repeated tests and was expressed as relative standard deviation. The results are shown in Table 4. The accuracy of the MSPE-UPLC-MS / MS method established in this experiment for determining each analyte was within ±10%, and the precision was within 15%, which met the test requirements.

[0092] Table 4 Accuracy and precision of the analytes in water samples determined by MSPE-UHPLC-MS / MS

[0093]

[0094]

[0095] 3. Absolute recovery rate

[0096] The absolute recovery rate is the ratio of the peak area of ​​the blank sewage after adding the standard substance and undergoing magnetic solid phase extraction to the peak area of ​​the standard substance directly diluted to assume 100% adsorption and elution. The pretreatment operation in step (2) was performed on sewage containing 15ng / L, 25ng / L, and 400ng / L of 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA, and MDMB-FUBICA, and the absolute recovery rate was investigated. The results are shown in Table 5. At different investigated concentration levels, the absolute recovery rates of each target were between 63.17% and 86.22%, indicating that the sewage matrix has a certain influence on the adsorption of the material.

[0097] Table 5 Absolute recovery of each analyte in water samples determined by MSPE-UPLC-MS / MS

[0098]

[0099]

[0100] 4. Matrix Effect

[0101] The matrix effect refers to the ratio of the UHPLC-MS / MS peak area of ​​the sample obtained by adding the standard substance to blank sewage for magnetic solid phase extraction to the sample of the corresponding concentration directly diluted to the standard substance after 100% adsorption elution. The pretreatment operation in step (2) was performed on sewage containing 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB-FUBICA 2.5ng / L, 80ng / L, and 200ng / L to investigate the matrix effect. The results are shown in Table 6. According to the results, sewage showed a matrix enhancement effect on 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA and MDMB-FUBICA.

[0102] Table 6 Matrix effects of various analytes in water samples determined by MSPE-UHPLC-MS / MS method (without isotope internal standard correction)

[0103]

[0104]

[0105] Example 3 Effect of the dosage ratio of Fe3O4@MWCNTs and GMA on the magnetic solid phase extraction adsorption efficiency of the target

[0106] The adsorption effects of 11 target substances (25ng / L, 80ng / L, 200ng / L) were investigated using different Fe3O4@MWCNTs and GMA dosage ratios. The specific operation of synthesizing the magnetic carbon fiber material is the same as that in Example 1, except that the dosage ratios of Fe3O4@MWCNTs and GMA in step (3) are different, namely 1:0.35, 1:0.7 and 1:1.4, and the dosages of TRIM and AIBN are adjusted with the dosage of GMA. The adsorption effects of the magnetic carbon fiber materials synthesized in different ratios were verified by the method described in Example 2. The results are as follows: Figure 6 show. Figure 6The results of the effect of different Fe3O4@MWCNTs and GMA dosage ratios on the magnetic solid phase extraction adsorption of the target in Example 3, where (a) is 25ng / L for 11 targets, (b) is 80ng / L for 11 targets, and (c) is 200ng / L for 11 targets. Figure 6 It can be seen that with the increase in the dosage of GMA and TRIM, the enrichment efficiency of magnetic carbon fiber materials for the target in sewage did not show an upward trend. When the dosage ratio of Fe3O4@MWCNTs and GMA increased to 200mg:280mg (mass ratio of 1:1.4), a large amount of transparent solid appeared in the reaction system, and the synthesized material lost its magnetism; the adsorption and elution effect was best when the dosage ratio was 200mg:70mg (mass ratio of 1:0.35). Therefore, in the subsequent experimental process, the dosages of Fe3O4@MWCNTs, GMA, TRIM and AIBN were 200mg:70mg:140mg:6mg respectively.

[0107] Example 4 Effect of Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesis time on the magnetic solid phase extraction adsorption efficiency of the target

[0108] The experimental process is the same as that of Example 3, and the preparation of the magnetic carbon fiber material is the same as that of Example 1, wherein the dosages of Fe3O4@MWCNTs, GMA, and TRIM are 200 mg, 70 mg, and 140 mg, respectively. The difference is that the synthesis time of the Fe3O4@MWCNTs@poly(GMA-co-TRIM) magnetic carbon fiber material in step (3) of Example 1 is different. The effect of different synthesis times of the magnetic carbon fiber material on the magnetic solid phase extraction efficiency of target analytes (25 ng / L, 80 ng / L, and 200 ng / L) in wastewater with different concentrations is studied, and the selected synthesis reaction times are 4 h, 8 h, 16 h, and 24 h, respectively. The results are shown in FIG. Figure 7 shown.

[0109] Figure 7 The results of the effect of different Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesis time on the magnetic solid phase extraction adsorption of the target in Example 4, where (a) is 25ng / L 11 kinds of targets, (b) is 80ng / L 11 kinds of targets, and (c) is 200ng / L 11 kinds of targets. Figure 7 It can be seen that the efficiency of magnetic solid phase extraction gradually increases within the reaction time of 4 to 24 h. When the reaction time is further extended to 24 h, the efficiency of magnetic solid phase extraction does not increase significantly. Therefore, the reaction time of 16 h is selected for subsequent experiments.

[0110] Example 5 Effect of pH value of sewage solution on adsorption effect of magnetic carbon fiber material

[0111] The present invention studies the effect of different pH values ​​of sewage solution on the adsorption effect of magnetic carbon fiber material. The magnetic carbon fiber material used is Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesized in Example 1. The adsorption and elution process is the same as step (2) in Example 2, except that the pH value of the sewage solution is adjusted to 2, 4, 6, 8, 10, 12, and 14 using dilute hydrochloric acid solution or sodium hydroxide solution. The results are as follows: Figure 8 shown. Figure 8 The results of the effect of the pH value of the sample sewage on the magnetic solid phase extraction adsorption in Example 5 are shown in FIG. Figure 8 It shows that when the pH value of the sewage solution is between 2 and 4, the adsorption effect on the target is basically the same, but when the pH value of the sewage solution is greater than 4, the adsorption effect of the magnetic carbon fiber material on 11 targets is decreasing. This is because when synthetic cannabinoid drugs are adsorbed in sewage, the hydrogen ions and hydroxide ions in the solution will affect the electrical properties and functional group state of the adsorbent surface and the adsorbed target, thereby affecting the interaction between it and the target. Therefore, the pH value of the solution is an important influencing factor. By adjusting the pH value of the solution, the best adsorption effect can be obtained. Therefore, the optimal pH value of the sewage solution selected in subsequent experiments is between 2 and 4.

[0112] Example 6 Effect of the amount of magnetic carbon fiber material and magnetic solid phase extraction adsorption time on the adsorption effect of magnetic carbon fiber material

[0113] The magnetic carbon fiber material Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesized in Example 1 was selected, and the pretreatment process was the same as step (2) in Example 2, except that different amounts of magnetic carbon fiber materials and different magnetic solid phase extraction times were selected to investigate the effects on the adsorption of synthetic cannabinoids in wastewater. The amounts of magnetic carbon fiber materials selected were 5 mg, 10 mg, 20 mg and 40 mg, respectively. The results are shown in FIG. Fig. 9 The results show that the optimal adsorption efficiency of synthetic cannabinoids in sewage is achieved when the amount of magnetic solid phase extraction material used reaches 20 mg. Therefore, 20 mg is selected as the optimal amount of magnetic solid phase extraction material in subsequent experiments. The selected solid phase extraction times are 5 min, 10 min, 20 min and 40 min, respectively. The results are as follows Fig.10 It was shown that the best adsorption efficiency was achieved when the magnetic solid phase extraction time was 20 min, so 20 min was selected as the optimal magnetic solid phase extraction time in subsequent experiments.

[0114] Example 7 Effect of eluent solvent type, solvent volume and elution time on magnetic solid phase extraction efficiency

[0115] The magnetic carbon fiber material Fe3O4@MWCNTs@poly(GMA-co-TRIM) synthesized in Example 1 was selected, and the pretreatment process was the same as step (2) in Example 2, except that the effects of different eluent solvent types, solvent volumes and elution times on the adsorption of synthetic cannabinoids in sewage were investigated. The single factor control method was used to investigate the eluent solvent type, solvent volume and elution time.

[0116] Pure methanol, pure acetonitrile, 1% ammonia methanol, acetonitrile with 1% ammonia water, 1% acetic acid methanol and acetonitrile with 1% acetic acid were selected as eluents to investigate the effect of the type of eluent on the extraction efficiency. The results are shown in Figure 2. Fig.11 As shown in the figure, the elution effects of pure methanol, 1% ammonia methanol, and 1% acetic acid methanol are all weaker than that of pure acetonitrile solution. Acetonitrile with the addition of 1% acetic acid and acetonitrile with the addition of 1% ammonia water do not improve the adsorption efficiency. Therefore, considering the experimental cost and adsorption efficiency, acetonitrile was used as the eluent in subsequent experiments.

[0117] The volume of the eluent has a great influence on the elution efficiency. When the volume of the eluent is too small, the target adsorbed on the magnetic carbon fiber material will not be completely eluted, while when the volume of the eluent is too large, the desorbed target will be diluted. Therefore, it is very important to choose a suitable amount of adsorbent. The eluent amounts selected by the present invention are 100μL, 300μL, 500μL and 1000μL respectively. The results are as follows: Fig.12 As shown in the figure, when the amount of acetonitrile selected as the eluent is 300 μL, the elution efficiency is the highest, which is the optimal eluent amount. Therefore, 300 μL is selected as the eluent amount in subsequent experiments. The selected elution times are 1 min, 2 min, 3 min and 4 min, respectively. The results are shown in the figure. Fig.13 As shown, the best effect was achieved when the elution time was 2 min, so 2 min was selected as the elution time for subsequent experiments.

[0118] Example 8 Effect of ionic strength on magnetic solid phase extraction efficiency

[0119] In order to study the effect of ionic strength in sewage on the enrichment of synthetic cannabinoids in sewage, the extraction efficiency of magnetic carbon fiber materials was studied using NaCl solutions of different concentrations. Fig.14 It shows that when the NaCl concentration increases, the extraction efficiency decreases, which may be because the added salt ions compete with the target for the target of the magnetic carbon fiber material. However, when the salt concentration is as high as 100mM, the degree of decrease in adsorption and elution efficiency is relatively low, indicating that the ions in the sewage have a weak effect on the efficiency of magnetic solid phase extraction.

[0120] Example 9 Effect of organic solvent content in sewage on magnetic solid phase extraction enrichment efficiency

[0121] There is a high possibility that there are small amounts of organic solvents in sewage in daily life. Therefore, it is of great significance to investigate the effect of its content on magnetic solid phase extraction. The organic solvent selected in the experiment is ethanol, which is the most common organic solvent in life. With a sample volume of 5 mL, solutions containing different proportions of ethanol (0%, 5%, 10%, 20%, 50%) were enriched and investigated. The results are as follows: Fig.15 As shown, when the ethanol content is within 20%, the effect on the target is an enhancement effect, while when the proportion reaches 50%, the effect on magnetic solid phase extraction is obvious. The possible reason is that the organic solvent molecules and the target may compete for adsorption on the adsorption sites of the magnetic extractant. When the organic solvent content in the sewage is high, a large number of organic solvent molecules may occupy the adsorption sites, making it difficult to effectively adsorb the target, thereby reducing the enrichment efficiency.

Claims

1. A magnetic carbon fiber material, characterized in that: The magnetic carbon fiber material is a core-shell structure of Fe3O4@MWCNTs@poly(GMA-co-TRIM); wherein Fe3O4 is located in the core, the outer layer of Fe3O4 wraps the core-shell MWCNTs formed by carboxylated multi-walled carbon nanotubes, and the outer part of the MWCNTs core-shell layer wraps the load layer of trimethylolpropane trimethacrylate cross-linked with polymethacrylate glycidyl.

2. The method for preparing the magnetic carbon fiber material according to claim 1, characterized in that: The following steps are involved: (A1) dissolving carboxylated multi-walled carbon nanotubes in deionized water and dispersing by ultrasonication to obtain a carboxylated multi-walled carbon nanotube suspension; (A2) dissolving ferric chloride hexahydrate and sodium dodecyl sulfate in deionized water, dissolving by ultrasonication, adding ferrous chloride tetrahydrate and carboxylated multi-walled carbon nanotube suspension, stirring to dissolve, adjusting the pH, stirring to react under nitrogen protection, separating and collecting under the action of an external magnetic field, washing with deionized water and anhydrous ethanol for multiple times, and vacuum drying to obtain Fe3O4@MWCNTs; (A3) Fe3O4@MWCNTs were dissolved in acetonitrile and dispersed by ultrasonic. Glycidyl methacrylate and trimethylolpropane trimethacrylate were added. The mixture was stirred and heated. 2,2-azobisisobutyronitrile was added. The mixture was heated and stirred for reaction. The mixture was washed with acetonitrile and deionized water for multiple times and vacuum dried to obtain Fe3O4@MWCNTs@poly(GMA-co-TRIM).

3. The method for preparing the magnetic carbon fiber material according to claim 2, characterized in that: In step (A1), the concentration of the carboxylated multi-walled carbon nanotube suspension is 0.08 g / mL.

4. The method for preparing the magnetic carbon fiber material according to claim 2, characterized in that: In step (A2), the mass ratio of ferric chloride hexahydrate, sodium dodecyl sulfate, ferrous chloride tetrahydrate and carboxylated multi-walled carbon nanotubes is (3-5):0.1:(1-3):(1-2), the pH is adjusted to 11±0.5, the stirring reaction time is more than 60 minutes under nitrogen protection, and the mixture is washed with deionized water and anhydrous ethanol for more than 3 times in sequence. The vacuum drying temperature is 60-70°C and the vacuum drying time is 8-16 hours.

5. The method for preparing the magnetic carbon fiber material according to claim 2, characterized in that: In step (A3), the mass ratio of Fe3O4@MWCNTs, glycidyl methacrylate, trimethylolpropane trimethacrylate and 2,2-azobisisobutyronitrile is 200:(70-280):(140-560):(6-24), the temperature is raised to 70±5°C with stirring, the temperature of the heating and stirring reaction is 70±5°C, the heating and stirring reaction time is 4-24h, the reaction is washed with acetonitrile and deionized water for more than three times, the vacuum drying temperature is 60-70°C, and the vacuum drying time is 8-16h.

6. Application of the magnetic carbon fiber material according to claim 1 in detecting synthetic cannabinoid drugs in sewage.

7. The use according to claim 6, characterized in that: Synthetic cannabinoid drugs include 4CN-CUMYL-BUTINACA, 4F-MDMB-BUTINACA, 5F-MDMB-PICA, 5F-MPP-PICA, AMB-4en-PICA, AMB-CHMICA, AMB-FUBICA, FUB-144, MDA-19, MDMB-4en-PINACA, and MDMB-FUBICA.

8. A method for detecting synthetic cannabinoid drugs in sewage, characterized in that: The following steps are involved: (B1) adding the magnetic carbon fiber material according to claim 1 to the wastewater with adjusted pH, extracting by uniform shaking, separating by adding a magnet, and eluting by adding an eluent to obtain an eluent; (B2) Ultrapure water was added to the eluent and used for UHPLC-MS / MS injection detection.

9. The detection method according to claim 8, characterized in that: In step (B1), the volume mass ratio of sewage to the liquid magnetic carbon fiber material according to claim 1 is 100: (5-40) mL / mg, the pH of the sewage is adjusted to 2-4, the eluent is acetonitrile, methanol, a mixture of ammonia water and methanol, a mixture of ammonia water and acetonitrile, acetic acid methanol and a mixture of acetic acid and acetonitrile, the uniform shaking extraction time is more than 20 minutes, the volume ratio of sewage to eluent is 100: (100-1000) mL / μL, and the elution time is 1-4 minutes.

10. The detection method according to claim 8, characterized in that: In step (B2), during UHPLC-MS / MS detection, the liquid chromatography conditions are as follows: the chromatographic column is Thermo BDS HYPERSIL C18; 0.1% formic acid aqueous solution is used as mobile phase A, and acetonitrile is used as mobile phase B; gradient elution: 0-4 min, 15→30% A, 4-5 min, 30% A, 5-7 min, 30→15% A, and the column temperature is 40°C; the flow rate is 0.3 mL / min; the injection volume is 10 μL; the mass spectrometry conditions are as follows: the ion source is an ESI electrospray ion source; the spray voltage is 3500 V; the sheath gas flow rate is 30 Arb; the auxiliary gas flow rate is 10 Arb; the ion transfer tube temperature is 325°C; the nebulization temperature is 150°C; and the scanning mode is MRM.